PERILAKU HOMOSEKSUAL DENGAN REALITAS PELACURAN DI RUMAH TAHANAN KELAS I CIPINANG - Albriyan Mohammad Fabriyanto; Mulyani Rahayu (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Homosexual behavior and prostitution are social phenomena often encountered in correctional facilities, including Cipinang Class I Penitentiary. This study aims to examine the relationship between homosexual behavior and the reality of prostitution occurring within the prison environment. The research uses a qualitative approach with in-depth interviews with inmates and prison staff. The findings show that environmental factors, loneliness, and economic needs are the primary causes of homosexual behavior and prostitution in Cipinang Prison. The limited conditions in prison create social dynamics that affect sexual behavior, both among inmates and with outsiders. Furthermore, economic factors also drive prostitution, where some inmates engage in such activities for financial gain. This study is expected to provide new insights into the social dynamics within correctional facilities and contribute to policy development to address prostitution and homosexual behavior in prisons.